2021
DOI: 10.1029/2021jc017486
|View full text |Cite
|
Sign up to set email alerts
|

Regionalization of the Red Sea Based on Phytoplankton Phenology: A Satellite Analysis

Abstract: The Red Sea is a marine biodiversity hotspot, surrounded by coral reefs and mangroves, which favors the development of specific ecological niches (Baars et al., 1998). Phytoplankton organisms in this basin, as in the rest of the global ocean, play a key role in pelagic marine ecosystem's functioning. Moreover, phytoplankton cells influence the production and vertical export of organic carbon, a key component of the carbon cycle that impacts the atmospheric concentration of CO 2 (Bopp and Le Quéré, 2009;Boyd et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 65 publications
0
8
0
1
Order By: Relevance
“…A community break could have been expected in our data as the Gulf of Aqaba and the northern Red Sea have been recently identified as two distinct bioregions (Kheireddine et al, 2021). This has been attributed to the phytoplankton phenology, which is linked to the physical conditions occurring in their respective areas.…”
Section: Symbiodiniaceae Genotypes Across Latitudesmentioning
confidence: 52%
See 1 more Smart Citation
“…A community break could have been expected in our data as the Gulf of Aqaba and the northern Red Sea have been recently identified as two distinct bioregions (Kheireddine et al, 2021). This has been attributed to the phytoplankton phenology, which is linked to the physical conditions occurring in their respective areas.…”
Section: Symbiodiniaceae Genotypes Across Latitudesmentioning
confidence: 52%
“…This supplies cold, nutrient-rich waters at the surface due to thermohaline circulation as well as wind forces (Kheireddine et al, 2021 and references therein). The northern Red Sea is influenced by the general cyclonic circulation observed in this area, as well as the permanent presence of mesoscale features (i.e., cyclonic and anticyclonic eddies) (Kheireddine et al, 2021;Papagiannopoulos et al, 2021). For example, in coastal areas where coral reefs are present, summer phytoplankton bloom can be observed due to local circulation features and the presence of corals that lead to an injection of nutrients within the surface layer (Papagiannopoulos et al, 2021).…”
Section: Symbiodiniaceae Genotypes Across Latitudesmentioning
confidence: 99%
“…We further found that the TMBAA for cluster II showed small changes over the entire period (Extended Data Fig. 9d), indicating relatively stable phenological cycles for those phytoplankton blooms 32,77 .…”
Section: Correlations With Sst and Sst Gradientmentioning
confidence: 66%
“…Kehidupan fitoplankton di perairan laut umumnya diatur oleh parameter oseanografi dalam hal ini parameter fisik (Kheireddine et al, 2021;Mikaelyan et al, 2020), kimia (Mishra et al, 2022;Neri et al, 2022), dan biologi (Mikaelyan et al, 2020). Sinergitas parameter itu mempengaruhi aktivitas fitoplankton, seperti halnya mempengaruhi produksi bahan organik melalui proses fotosintetis (Mohammed et al, 2018;Petrou et al, 2016), demikian pula berpengaruh terhadap distribusinya berdasarkan ruang dan waktu (Tambaru et al, 2021;Khan et al, 2015).…”
Section: Pendahuluanunclassified